Analysis of the Needs for a Language Learning Model Based on Multiple Intelligences with the Integration of Maluku Culture - Wilma Akihary; Iwan Rumalean; Wenda Marlin Kakerissa; Areni Yulitawati Supriyono; Kevin Moses Selano; Imanuel Joseph; Pietma Maspaitella (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Contemporary language learning requires a learner-centered approach that is responsive to cognitive diversity and learners’ cultural backgrounds. This study aims to analyze the needs of students and lecturers regarding the development of a Multiple Intelligences (MI)-based language learning model integrated with Maluku culture. A descriptive-exploratory survey design was employed, involving 108 students and 21 lecturers from the Department of Language and Arts at Pattimura University. Data was collected through a structured questionnaire assessing awareness, preferences, readiness, and the need for institutional support, and were analyzed using descriptive statistics. The findings indicate that students demonstrate a high level of awareness of multiple intelligence, a strong preference for creative, multimodal, and project-based learning, and a positive attitude toward the integration of local culture in language learning. Meanwhile, lecturers exhibit strong support for the implementation of MI-based pedagogy and culturally responsive teaching; however, they still face constraints related to the availability of learning resources and institutional support. These findings underscore the importance of developing a language learning model that contextually integrates multiple intelligences and local culture. Theoretically, this study contributes by integrating the MI approach and culture-based pedagogy within a needs analysis framework, which have often been examined separately. Practically, the findings provide a foundation for the development of more inclusive, contextual, and learner-responsive language curricula and instructional designs.